Combined influence of healthy diet and active lifestyle on cardiovascular disease risk factors in adolescents. Issue 3 (12th December 2012) - Cuenca‐García, M.; Ortega, F. B.; Ruiz, J. R.; González‐Gross, M.; Labayen, I.; Jago, R.; Martínez‐Gómez, D.; Dallongeville, J.; Bel‐Serrat, S.; Marcos, A.; Manios, Y.; Breidenassel, C.; et al.
<x xml:space="preserve">Abstract</x> To investigate the combined influence of diet quality and physical activity on cardiovascular disease (CVD) risk factors in adolescents, adolescents (n = 1513; 12.5–17.5 years) participating in the Healthy Lifestyle in Europe by Nutrition in Adolescence study were studied. Dietary intake was registered using a 24‐h recall and a diet quality index was calculated. Physical activity was assessed by accelerometry. Lifestyle groups were computed as: healthy diet and active, unhealthy diet but active, healthy diet but inactive, and unhealthy diet and inactive. CVD risk factor measurements included cardiorespiratory fitness, adiposity indicators, blood lipid profile, blood pressure, and insulin resistance. A CVD risk score was computed. The healthy diet and active group had a healthier cardiorespiratory profile, fat mass index (FMI), triglycerides, and high‐density lipoprotein cholesterol (HDL‐C) levels and total cholesterol (TC)/HDL‐C ratio (all P ≤ 0.05). Overall, active adolescents showed higher cardiorespiratory fitness, lower FMI, TC/HDL‐C ratio, and homeostasis model assessment index and healthier blood pressure than their inactive peers with either healthy or unhealthy diet (all P ≤ 0.05). Healthy diet and active group had healthier CVD risk score compared with the inactive groups (all P ≤ 0.02). Thus, a combination of healthy diet and active lifestyle is associated with decreased CVD risk in adolescents. Moreover, an active lifestyle may reduce the adverse consequences of an unhealthy diet.